+0  
 
+1
165
1
avatar+2507 

Help

NotSoSmart  Nov 20, 2017
Sort: 

1+0 Answers

 #1
avatar+86643 
+1

2x^2 -3x + 2  = 0

 

a = 2, b  = -3, c =  2

 

 

x  =    ( -(-3) ±√[ (-3)^2 - 4(2) (2) ]  ) /  [2*2 ] 

 

x  =     ( 3 ±√ [ 9 - 16 ]  ) / 4

 

x =  ( 3 ± i√ 7 )  / 4

 

 

cool cool cool

CPhill  Nov 20, 2017

5 Online Users

avatar
New Privacy Policy (May 2018)
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  Privacy Policy